A NEW CYTOTOXIC DOLABELLANE FROM THE INDONESIAN SOFT CORAL Anthelia sp. - Anggia Murni; Novriyandi Hanif; Junichi Tanaka (Universitas Gadjah Mada, 2013)
One new dolabellane (1) and two known diterpenoids stolonidiol (2) and clavinflol B (3) have been isolated from the ethyl acetate extract of the Indonesian soft coral Anthelia sp. A new compound 1 exhibited a moderate cytotoxicity against NBT-T2 cells at 10 µg/mL, while known compounds 2 and 3 showed cytotoxicity at 1 and 0.5 µg/mL, respectively. Structure of the new compound 1 was elucidated by interpretation of NMR spectroscopic data (1D and 2D NMR data) and mass spectrometry (ESIMS data) as well as comparison with those of related ones. This finding should be useful for anti cancer drug development of the promising dolabellane-types compound.